1977
DOI: 10.1530/acta.0.0840538
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Long-Term Antithyroid Treatment of Graves' Disease in Relation to Iodine Intake

Abstract: Seventy-seven patients with Graves' disease, with an average of 56 years of age were treated with carbimazole in the period 1968\p=n-\1975. The duration of therapy was on an average, 17.9 months and the follow-up on an average, 28.5 months. Remission was found only in 32 % of the patients. Data on the urinary iodine excretion from a total of 127 euthyroid controls and 15 patients with Graves' disease living in the same area were collected

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…In summary, although all workers do not agree, the presence of TSH receptor antibodies, especially when considered in relation to clinical and thyroid hormone parameters at the termination of a course of antithyroid medications, usually heralds return of the disease whereas lack of such antibodies may be used as a general predictor of remission (308)(309)(310)(311)(312). Reported remission rates after a trial of antithyroid medications (usually 6-18 months) vary greatly, perhaps from 17 to 85% (313)(314)(315). Wartofsky (314) and Lumholtz et al (315) have speculated that part of the variability may be related to dietary iodine intake with higher relapse rates associated with increased dietary intake.…”
Section: Correlations Between Different Types Of Tsh Receptor Antibodmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, although all workers do not agree, the presence of TSH receptor antibodies, especially when considered in relation to clinical and thyroid hormone parameters at the termination of a course of antithyroid medications, usually heralds return of the disease whereas lack of such antibodies may be used as a general predictor of remission (308)(309)(310)(311)(312). Reported remission rates after a trial of antithyroid medications (usually 6-18 months) vary greatly, perhaps from 17 to 85% (313)(314)(315). Wartofsky (314) and Lumholtz et al (315) have speculated that part of the variability may be related to dietary iodine intake with higher relapse rates associated with increased dietary intake.…”
Section: Correlations Between Different Types Of Tsh Receptor Antibodmentioning
confidence: 99%
“…Reported remission rates after a trial of antithyroid medications (usually 6-18 months) vary greatly, perhaps from 17 to 85% (313)(314)(315). Wartofsky (314) and Lumholtz et al (315) have speculated that part of the variability may be related to dietary iodine intake with higher relapse rates associated with increased dietary intake. We are unaware of studies investigating the role of iodide in immune modulation.…”
Section: Correlations Between Different Types Of Tsh Receptor Antibodmentioning
confidence: 99%
“…Such supplementation may lead to median iodine excretion values that seem reasonable, even if the iodine intake of the part of the population not taking iodine (in this study, nearly half of the population) is low. Klaus Pedersen, Department of Internal Medicine and Endocrinology, Aalborg Hospital, Reberbansgade, DK-9000 Aalborg, Denmark A number of studies have shown that the iodine intake is relatively low in Denmark (1)(2)(3)(4), possibly with a tendency to increasing values (4). However, the interpretation of the previous studies is difficult owing to the lack of knowledge on the frequency of individual iodine supplementation in the form of daily intake of iodine-containing vitamin/mineral tablets.…”
mentioning
confidence: 99%
“…In the Copenhagen area an iodine excretion of 87.4 µg/24 h (arithmetric mean: a.m.) was meas¬ ured in 93 healthy controls by Lumholtz et al (1977) and of 100 µg/24 h (a.m.) in 16 men by M0lholm Hansen et al (1975). So it appears that the iodine excretion in Funen in 1985 is approxi¬ mately at the same level as the values from the Copenhagen area 8-10 years ago.…”
Section: Discussionmentioning
confidence: 73%